Perilaku Higiene Pengolah Makanan Berdasarkan Pengetahuan Tentang Higiene Mengolah Makanan Dalam Penyelenggaraan Makanan Di Pusat Pendidikan Dan Latihan Olahraga Pelajar Jawa Tengah - Suci Fatmawati; Ali Rosidi; Erma Handarsari (Jurnal Gizi, 2013)
Implementation of food hygiene and healthy food into basic principles of foodservices. Workers especially food processors play an important role in the smooth running of the production process because workers are planners, implementers and managers in an organization of food services. There are four (4) factors that allow the transmission of disease through the food hygienic behavior, a source of infectious diseases, the media (food, drinks) and recipient-recipient. The purpose of this study was to determine hygiene behavior based on knowledge about food hygiene in the operation of food processing food in Sports Training and Education Center Student Central Java.  This type of research is descriptive approach used is cross sectional (cross-sectional), where the cause and effect variables were measured at the same time. The samples were all food processors in Sports Training and Education Center Student Central Java, amounting to 6 people. The results showed that 50% of respondents had a good knowledge and behavior of respondents with categories are as many as 3 people (50%). Food processing knowledge is good enough, but seen from the behavior of food processors still less attention to hygiene of food processing. This shows that there is no relation between hygiene knowledge of food processing food processing hygiene behavior.Key word : knowledge and hygiene behavior of food processor